2005
DOI: 10.1142/s0192415x05003028
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory Activity of Herbal Medicines: Inhibition of Nitric Oxide Production and Tumor Necrosis Factor-α Secretion in an Activated Macrophage-like Cell Line

Abstract: Houttuynia cordata Thunb. (HC), Glycyrrhiza uralensis Fischer (GU), Forsythia suspense (Thunb.) Vahl (FS), and Lonicera japonica Thunb. (LJ) are Chinese herbs known to possess anti-inflammatory properties. The effects of aqueous extracts of these herbs on the production of the pro-inflammatory mediators, nitric oxide (NO) and tumor necrosis factor-alpha (TNF-alpha) were examined in an activated macrophage-like cell line, RAW 264.7 cells. Aqueous extracts from FS at 0.0625-2.0 mg/ml inhibited in vitro productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
78
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(82 citation statements)
references
References 24 publications
3
78
0
1
Order By: Relevance
“…(Caprifoliaceae) is commonly used as an anti-inflammatory herbal medicine in China. 1,2) We found that L. japonica produced in Henan and Shandong Provinces has the most potent anti-inflammatory effect.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…(Caprifoliaceae) is commonly used as an anti-inflammatory herbal medicine in China. 1,2) We found that L. japonica produced in Henan and Shandong Provinces has the most potent anti-inflammatory effect.…”
mentioning
confidence: 91%
“…(Caprifoliaceae) is commonly used as an anti-inflammatory herbal medicine in China. 1,2) We found that L. japonica produced in Henan and Shandong Provinces has the most potent anti-inflammatory effect.3) The herbs grown in these two provinces are recognized as geo-authentic and possess a higher content of therapeutically effective components in the flowers.4) The ecological factors for the cultivation of geo-authentic L. japonica have been studied.5) We attempted to classify the geo-authentic L. japonica by microscopic and chemical characteristics, but because these factors are not well-established, it was difficult to identify specific criteria to distinguish the geo-and non-authentic varieties of L. japonica. …”
mentioning
confidence: 99%
“…5) In experimental studies, H. cordata exhibited antibacterial activity, antileukemic activity, antiinflammatory activity, anaphylactic reaction and mast cell activation, and modulated nitric oxide (NO) production. [6][7][8][9][10] However, to date, studies to understand the other antibacterial effects, including the intracellularly replicating pathogens of these plants, are lacking.The mammalian immune response is divided broadly into the innate and adaptive responses. Innate immune responses of mammals involve the first line of defense against invading microorganisms, including the release of antimicrobial peptides at epithelial surfaces, phagocytosis, and intracellular killing of microorganisms by phagocytes and the activation of the complement cascade.…”
mentioning
confidence: 99%
“…The intrinsic pathway involves the signals to mitochondria, which lead to the release of cytochrome c, Apaf-1, AIF and pro-caspase-9, and then combine with Apaf-1 and pro-caspase-9 to form the apoptosome (11,13,14). Park et al demonstrated that HCT inhibited nitric oxide (NO) production in a dose-dependent manner, but minimally inhibited TNF-· secretion at 0.0625 and 0.125 mg/ml on macrophage-like cell line (RAW 264.7 cells) (37).…”
Section: Discussionmentioning
confidence: 99%